2023
DOI: 10.1002/mabi.202200460
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cell Penetration and Pluripotency Maintenance of hiPSCs in 3D Natural Chitosan Scaffolds

Abstract: Human‐induced pluripotent stem cells (hiPSCs) cultured in 3D matrices hold great promise in disease modeling, drug discovery, and tissue regeneration. Uniform cell distribution in a 3D structure is critical to the growth and function of hiPSCs, yet cell seeding in 3D matrices often remains superficial, leading to limited cell proliferation and compromised pluripotency. Here, an approach to improve cell penetration depth of hiPSCs in 3D scaffolds modified with hiPSCs conditioned medium (CM) is reported. It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Additionally, we assessed the surface charge of the chitosan scaffold across a pH range of 6.5–8.5 (Figure d). Prior studies have indicated that chitosan scaffolds with near-neutral charge enhance the adhesion and proliferation of human neural stem cells, outperforming negatively charged collagen scaffolds and chitosan–hyaluronic hybrid scaffolds. , Additionally, it has been reported that pure chitosan materials enhance the proliferation and pluripotency of hiPSCs. , Here, the zeta potential of our chitosan scaffolds showed minimal variation, maintaining near-neutrality despite changes in pH, which suggests a favorable setting for iPSCs attachment.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Additionally, we assessed the surface charge of the chitosan scaffold across a pH range of 6.5–8.5 (Figure d). Prior studies have indicated that chitosan scaffolds with near-neutral charge enhance the adhesion and proliferation of human neural stem cells, outperforming negatively charged collagen scaffolds and chitosan–hyaluronic hybrid scaffolds. , Additionally, it has been reported that pure chitosan materials enhance the proliferation and pluripotency of hiPSCs. , Here, the zeta potential of our chitosan scaffolds showed minimal variation, maintaining near-neutrality despite changes in pH, which suggests a favorable setting for iPSCs attachment.…”
Section: Resultsmentioning
confidence: 60%
“…The resulting solution was cast into commercial tissue culture microplates, refrigerated at 4 °C for 1 h, at −5 °C for 20 min, at −20 °C for 1 h, and then anneal at −2 °C for 2 h, followed by lyophilization using a SP VirTis Genesis Pilot lyophilizer (SP Scientific, USA). 30 Prior to cell seeding, the chitosan scaffolds were sectioned into 400 μm slices and disinfected with 70 and 90% ethanol, followed by rinsing with PBS 3 times for 10 min each. After the disinfection process, the scaffolds were transferred into a 24-well plate, ready for cell seeding.…”
Section: Fabrication Of Chitosan Porous Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation